GaN Schottky diode on sapphire substrate for THz frequency multiplier applications - Di Gioia, Giuseppe; Samnouni, Mohammed; Chinni, Vinay; Mondal, Priyanka; Treuttel, Jeanne; Zegaoui, Malek; Ducournau, Guillaume; Zaknoune, Mohammed; Roelens, Yannick (Micro and nanostructures (2022), 2022)
Gallium Nitride, because of its high breakdown field, and peak and saturated electron drift velocity, high chemical stability and high thermal conductivity, is a very promising material as candidate for Schottky varactor diodes for next-generation high-power frequency multipliers. Similarly to the huge interest in the field of HEMT for high frequency and power application, GaN Schottky diodes is of a high interest for the next technological step for frequency multipliers for THz generations, replacing GaAs Schottky diodes. Due to a lack of research focused on GaN Schottky diodes for frequency multiplication, the design and fabrication of GaN frequency multipliers remains a technological challenge. In this paper, we present GaN Schottky diodes fabricated on a heteroepitaxial GaN on sapphire. The barrier height obtained is around 0.53 eV, and it increases up to 0.73 eV after Schottky contact annealing; and the ideality factor is equal to 1.1 before annealing and 1.2 after annealing. The resulting series resistance is very low, 7Ω and 1Ω, before and after annealing, respectively. © 2021 Elsevier Ltd